ASSESSING THE IMPACT OF INFORMATION TECHNOLOGY ON ACCOUNTING PERFORMANCE: A REVIEW STUDY - Ali Jawad Kadem (Scholar Express Journals, 2025)
The purpose of the current research is to review a set of previous literature to determine the extent to which the impact of information technology on accounting performance is evaluated, through the analysis of a set of articles to understand the intellectual and conceptual trends and developments of previous studies, in light of the statement of objectives, type, sample and results of each study, in the light of which the extent of the relationship between this study and previous studies is determined, as well as understanding how information technology affects accounting performance contributes to improving computerized accounting systems and speeding up reporting processes. Financial and accounting carried out by companies, in addition to contributing to forecasting in data analysis tools and accounting programs by improving the ability to analyze financial information faster and using information technology to predict future financial trends and provide the best suggestions, and as a result, study came out with a set of results, foremost of which was that information technology contributes to improving computerized internal control mechanisms, which contributes to improving accounting performance through compliance with accounting standards, laws and legislation. Financial.
Keywords: Information Technology; Accounting Performance